How the earth feels : geological fantasy in the nineteenth-century United States - Luciano, Dana (Durham : Duke University Press, 2024)
"By the start of the nineteenth century, the impact of the geological sciences and advancements in the field had radically expanded people's perception of the Earth's age. In How the Earth Feels, Dana Luciano maps the emergence of a "geological fantasy," in which increased knowledge of planetary life was used to racialize Native peoples as fossils and curiosities. Further, the geological fantasy served to cement the notion that the Earth had been preparing for the presence of humans, and that humans were in fact the ultimate expression of the Earth's teleological development in a both scientific and spiritual sense. Counterposing a range of texts-from early European and US geological texts to Indigenous accounts of earthquakes to African American men's anti-slavery writing featuring geological tropes-Luciano reveals the workings of the geological fantasy as it operated across the racial and biopolitical discourses of the nineteenth-century United States. Luciano offers a rich and historically nuanced account of how imagined relations with the non-human world have long served as a means of avoiding engagement with the dynamics of racial and colonial power"--
The "Fashionable Science" -- "The Infinite Go-Before of the Present": Geological Time, Worldmaking, and Race in the Nineteenth Century -- Unsettled Ground: Indigenous Prophecy, Geological Fantasy, and the New Madrid Earthquakes -- Romancing the Trace: Ichnology, Affect, Race -- Matters of Spirit: Vibrant Materiality and White Femme Geophilia -- The Natural History of Freedom: Blackness, Geomorphology, Worldmaking -- Ishmael's Anthropocenes and Others: Geological Fantasy in the Twenty-first Century.
Description based on print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Geology in literature; Geology -- Social aspects -- United States -- History -- 19th century; Geology -- United States -- History -- 19th century; American literature -- History -- 19th century; Géologie dans la littérature.; Géologie -- Aspect social -- États-Unis -- Histoire -- 19e siècle.; Littérature américaine -- Histoire -- 19e siècle.; HISTORY / Modern / 19th Century; NATURE / Environmental Conservation & Protection; American literature; Geology; Geology in literature; Geology -- Social aspects; United States; 1800-1899; History